Educational Policy Analysis: Examining Pesantren Policies and Their Implications on the Independence of Kyai and Pesantren in the Contemporary Era - Nadhif Muhammad Mumtaz; Evi Muafiah; Doli Witro (Jurnal Pendidikan Agama Islam)
Purpose – This study aims to investigate the autonomy of “Kyai” (religious teachers) within Pesantren in making education policy. In examining these policies, it focuses on the evolution of teaching and the implementation of the “Asas Tunggal Pancasila” in Indonesian educational institutions, the struggles of Pesantren policies that led to the birth of Law No. 18 of 2019, and the dark side of the politicization of religion that has implications for educational policies.